Investigating Test Equating Methods: English Examination Test - Rezkilaturahmi Rezkilaturahmi; Rahmat Danni; Heri Retnawati (Universitas Muhammadiyah Mataram, 2024)
The assessment is carried out in order to open up learning. The instruments used must of course carry out a good development stage process. The purpose of this study is to ensure reliable and fair test items in each educational unit. This research uses a quantitative approach which focuses on the equating method School Examination test equipment especially for English language subjects at the high school level in Muna district which has 2 schools. Data collection was carried out through documentation of student responses on the School Examination for English subjects. Student responses came from 2 question packages from 2 middle schools in Muna District. In addition, there were a total of 96 students involved in the school exam with each SMA 1 having 56 students and SMA 2 having 40 students. There were only 2 high schools of the same level in the Tongkuno area, especially Muna Regency, and took the question packages from the same source. Data were analyzed using an equating technique based on Item Response Theory with the mean-mean method. Item parameter estimation and equalization were used with the help of R Studio and Microsoft Excel programs. Therefore, R Studio is used to estimate the validity and reliability of the two question packages while Microsoft Excel is used to equalize the 2 different scores. The equating results in an equalization constant that ensures the two test packages now have scores that can be compared more fairly and accurately. Thus, these findings show the importance of the equating process in improving the integrity of educational evaluation in Indonesia especially to ensuring equivalence in two different packages is crucial to produce equal and fair score results.